2018
DOI: 10.12783/dtssehs/ichss2017/19557
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Paternalistic Leadership on Employee Voice Behavior: The Study of the Mediating Role of OBSE

Abstract: Abstract. As the research on the relationship between leadership behavior and employee voice behavior has generally been viewed from Western context (e.g., transformational leadership), few existing studies is rooted in Chinese culture. We investigated how the three components of paternalistic leadership, namely benevolence, moral and authoritarianism, influenced employee voice behavior through their impacts on organization-based self-esteem (OBSE). Using a sample of 347 employees, our results showed that thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Secondly, the results of the two-by-two correlations between the variables show that autocratic leadership is a relatively negative leadership style that also brings negative experiences to employees (Sun, 2014;Attridge, 2009) and is therefore significantly negatively correlated with the rest of the variables or dimensions, while benevolent, virtuous and strict leadership styles are significantly and positively correlated with psychological capital and employee engagement, suggesting that good leadership style is one of the main factors that promote high psychological well-being, higher performance and engagement of employees (Xiao, 2014;Liu & Wang, 2015). In addition, this study found that psychological capital showed a significant positive correlation with employee engagement, which is consistent with previous research findings that psychological capital, as a positive psychological state of individuals, will help to stimulate employees' creativity (Huang & Luthans, 2014;Rego et al, 2012), and consequently enhance individuals' professional engagement and promote their work performance and enhance individual career engagement (Wu et al, 2020;Luthans et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, the results of the two-by-two correlations between the variables show that autocratic leadership is a relatively negative leadership style that also brings negative experiences to employees (Sun, 2014;Attridge, 2009) and is therefore significantly negatively correlated with the rest of the variables or dimensions, while benevolent, virtuous and strict leadership styles are significantly and positively correlated with psychological capital and employee engagement, suggesting that good leadership style is one of the main factors that promote high psychological well-being, higher performance and engagement of employees (Xiao, 2014;Liu & Wang, 2015). In addition, this study found that psychological capital showed a significant positive correlation with employee engagement, which is consistent with previous research findings that psychological capital, as a positive psychological state of individuals, will help to stimulate employees' creativity (Huang & Luthans, 2014;Rego et al, 2012), and consequently enhance individuals' professional engagement and promote their work performance and enhance individual career engagement (Wu et al, 2020;Luthans et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study found that psychological capital mediates the relationship between paternalistic leadership and employee engagement. The results of the mediating effect test showed that both the direct and mediating effects of benevolent leadership were significant, while the direct path effects of the remaining three styles of paternalistic leadership on employee engagement were not significant, but the mediating effects were all significant, which may result from employees, the caring and support of a "motherly" leader has a more direct impact than a "fatherly" management image (Mao et al, 2020;Tang, 2011;Xiao, 2014), and the impact of benevolent leaders on employees' engagement behavior is shown in a direct way. However, the various styles of paternalistic leadership generally influence the level of employee engagement most of all through the mediate of psychological capital; it is believed that this internal mechanism can be explained by the interpersonal social exchange theory mentioned earlier in this paper, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary determinant of the factors that determine the level of voice, such as reward and punishment systems, decision-making approaches, and one-way or two-way communication implemented in the organization, is the organization’s leader (Xiao & Pan, 2017; Zhang et al, 2015). In other words, it is stated that there is a close relationship between the dominant leadership understanding in the organization and the voice of the employee (Dedahanov et al, 2016; Morrison & Milliken, 2000).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%